Lincoln Cathedral
The Front at Lincoln is one of nine black Tournai stone fonts in England. Imported from Belgium in the middle twelfth century, it belongs to the old Romanesque building. Beyond it may be seen the arcading of the aisle walls, which represents yet another advance in form from the pointed arch. This arcading was executed during the bishopry of Robert Grosseteste, who continued the building and who, between 1215 and 1235, wrote an important treatise on optics, in which he referred to light as the :most notable of natural phenomena."